Liquid core fiber and low PM10 emission friction material based on liquid core fiber
By using liquid core fibers in friction materials, the viscous liquid released during wear is used to reduce PM10 dust emissions, and enhance noise absorption performance through damping, the problem of excessive dust emissions of existing friction materials is solved, and the strictness is met environmental protection requirements.
Patent Information
- Application Number
- CN202411530881.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The PM10 dust emissions generated by existing automotive friction materials are relatively high during use, which is difficult to meet the increasingly stringent environmental protection regulations.
Liquid core fiber is used as a key component of friction material. The liquid core fiber is filled with heavy oil by hollow carbon fiber or hollow Elostone nanotubes and is coated with epoxy resin. The viscous liquid released during wear reduces dust emissions and passes damping. Enhance noise absorption effect.
It significantly reduces the PM10 dust emissions of friction materials, meets strict environmental protection requirements, and improves the noise absorption performance of friction materials.
Smart Images

Figure BDA0005110446880000101
Abstract
Description
Technical Field
[0001] The present invention relates to a plurality of technical fields such as composite materials and environmental protection, and in particular to a liquid core fiber and a low PM10 emission friction material based on the liquid core fiber. Background Art
[0002] During use, automotive friction materials need to withstand alternating positive pressure, shear stress and braking heat. Under the combined effect of these factors, wear will occur. Usually, most of the wear products will be discharged into the air in the form of PM10, which will cause air pollution. In recent years, with the increase in environmental awareness, countries have put forward requirements for the dust emission of automotive friction materials during use. For example, the current Euro 7 standard for passenger car PM10 friction dust emission requirements is 7mg / km, and it must reach 3mg / km by 2035. Such stringent regulations have brought huge challenges to the research and development of friction materials.
[0003] At present, the friction materials on the market are generally divided into organic asbestos-free metal-free friction materials and low-metal or semi-metal friction materials. Among them, organic asbestos-free metal-free friction materials are mainly reinforced with aramid, mineral fibers, etc. as the matrix, while low-metal or semi-metal friction materials are mainly reinforced with various metal fibers as the matrix. The filling materials of friction materials generally include barite, alumina, calcium carbonate, graphite, coke, sulfide, etc. These materials play an important role in maintaining structural strength and providing friction and wear performance, but they will also cause wear and tear during the braking friction process, forming wear debris. The detached wear products are in the form of fine particles, which is the main cause of air pollution. Therefore, it is urgent to develop a friction material with low PM10 emissions, so as to reduce the air pollution caused by the friction plate during use and better meet regulatory requirements. Summary of the invention
[0004] The main purpose of the present invention is to solve the above problems existing in the prior art and provide a low PM10 emission friction material based on liquid core fiber. The viscous liquid released when the liquid core fiber is worn can reduce the dust emission of the friction material, so that it can meet the increasingly stringent environmental protection requirements. At the same time, the liquid in the liquid core fiber also has a damping effect, which can significantly enhance the noise absorption effect of the friction material. To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0005] A liquid core fiber comprises a hollow fiber and a liquid, wherein the liquid is filled in the cavity inside the hollow fiber.
[0006] Furthermore, the liquid core fiber also includes epoxy resin, and the epoxy resin is coated on the surface and both ends of the hollow fiber to prevent the liquid inside from being released prematurely.
[0007] Furthermore, the hollow fiber is selected from at least one of hollow carbon fiber and hollow halloysite nanotube, and the liquid is heavy oil. Hollow carbon fiber and hollow halloysite nanotube have the advantages of high strength and good wear resistance. After absorbing heavy oil, they can improve friction and wear performance and reduce PM10 emissions. They have better adsorption effects on wear debris particles with coarse particle size (5-10um) and fine particle size (<5um), respectively.
[0008] The present invention also provides a method for preparing the liquid core fiber. The specific process is as follows: placing hollow carbon fibers or hollow halloysite nanotubes in a closed container, evacuating the container, adding high-temperature heavy oil for adsorption, and finally adding epoxy resin to coat and cap the hollow fibers.
[0009] Furthermore, the temperature of the high-temperature heavy oil is 80-120°C, and the adsorption is carried out at this temperature.
[0010] Furthermore, the epoxy resin is specifically a liquid UV-curable epoxy resin, including bisphenol A epoxy resin and alicyclic epoxy resin, etc. After the epoxy resin is added, the mixture is taken out from the sealed container and dispersed, and then irradiated with UV light to fully cure it.
[0011] The third object of the present invention is to provide a low PM10 emission friction material based on liquid core fiber, the friction material comprising liquid core fiber, adhesive, friction modifier and friction filler.
[0012] Furthermore, the adhesive is specifically graphene-enhanced polyimide resin particles, 100% of which pass through a 320-mesh screen. The resin is selected because it has the advantages of high temperature resistance and low wear, and can reduce the wear rate of the friction material and the wear of the material itself.
[0013] Furthermore, the content of graphene in the graphene-enhanced polyimide resin is 0.5wt%-1wt%, and the selected graphene is specifically graphene oxide with a particle size of less than 1 micron.
[0014] Furthermore, the friction modifier is selected from at least one of stannous sulfide, graphite flakes, and nano silicon carbide wafers.
[0015] Furthermore, the diameter of the nano silicon carbide wafer is 0.1 mm to 0.3 mm, and the thickness is 300 to 500 nm. The nano silicon carbide wafer can play a two-dimensional reinforcing role, preventing abrasive particles from invading the surface of the friction material, thereby improving the ability to resist abrasive particles and fatigue wear.
[0016] Furthermore, the friction filler is selected from at least one of barium sulfate and potassium sodium hexatitanate.
[0017] Furthermore, the friction material comprises, by weight, 13-33 parts of liquid core fiber, 10-15 parts of adhesive, 15-30 parts of friction modifier, and 25-55 parts of friction filler.
[0018] Furthermore, the friction material comprises, by weight: 10-15 parts of liquid core carbon fiber, 3-8 parts of liquid core halloysite nanotubes, 10-15 parts of graphene-enhanced polyimide resin, 5-10 parts of stannous sulfide, 5-10 parts of phosphorus flake graphite, 5-10 parts of nano silicon carbide chips, 10-25 parts of barium sulfate, and 15-30 parts of potassium sodium hexatitanate.
[0019] A fourth object of the present invention is to provide a method for preparing the above-mentioned friction material with low dust emission, comprising: preparing raw materials according to a formula, mixing the raw materials and then molding them.
[0020] Furthermore, the raw materials are mixed uniformly in a high-speed mixer, the speed of mixing is 2000-5000 rpm, the mixing time is 3-5 minutes, the temperature during molding is 135-150°C, and the pressure is 200-500 kg / cm 2 The molding time is 3-10 minutes, and the green body obtained by molding is placed at 145-160° C. for curing for 2-5 hours to obtain a friction material with excellent performance.
[0021] In order to solve the environmental pollution problem caused by dust emission during the use of friction materials, the inventors prepared a liquid core fiber and used it as the key and core component of the friction material. When the friction material wears, the liquid core fiber will break and release viscous liquid, which is used to bond fine wear debris particles into large particles and discharge them from the friction surface. Since the liquid is released synchronously with the wear process, this effect will continue with the wear, providing continuous cohesion on the friction surface to ensure that the function of reducing PM10 is continuously effective. When braking is completed, the transfer of wear debris and friction interface will cover the friction surface, thereby covering the wear end face of the hollow fiber tube and protecting the liquid in the tube.
[0022] Compared with the existing similar technologies, the advanced effects of the present invention are mainly reflected in the following aspects:
[0023] (1) The low dust emission friction material provided by the present invention uses graphene-enhanced polyimide resin as a bonding component, and is reinforced with liquid-core carbon fiber and liquid-core halloysite nanotubes, respectively. During normal use, the liquid in the liquid-core fiber plays a damping role, which significantly improves the noise absorption function of the friction material.
[0024] (2) The liquid-core carbon fiber and liquid-core halloysite nanotubes in the low dust emission friction material formula of the present invention also play a key role in reducing fine particle dust emissions. They mainly utilize the large amount of viscous liquid released during normal wear to aggregate and bond fine wear debris particles into particles larger than PM10, thereby preventing PM10 pollution in the air.
[0025] (3) The low dust emission friction material has a simple preparation process and excellent performance. While ensuring the friction performance of the friction material, it greatly reduces the emission of PM10 dust particles and meets the stringent environmental protection requirements of various countries. DETAILED DESCRIPTION
[0026] In order to enable ordinary technicians in the field to fully understand the technical solutions and beneficial effects of the present invention, further description is given below in conjunction with specific embodiments.
[0027] Example 1
[0028] The formulation of the low dust emission friction material is:
[0029] 10 parts of liquid core carbon fiber;
[0030] 3 parts of liquid core halloysite nanotubes;
[0031] 15 parts of graphene-enhanced polyimide resin;
[0032] 20 parts of barium sulfate;
[0033] 22 parts of potassium sodium hexatitanate;
[0034] 10 parts of stannous sulfide;
[0035] 10 parts of phosphorus flake graphite;
[0036] 10 nano-SiC wafers (0.2 mm in diameter, about 350 nm in thickness).
[0037] The preparation and method of the low dust emission friction material are as follows:
[0038] (1) 0.5 parts of graphene oxide with a particle size of less than 1 μm and 99.5 parts of polyimide resin are added to a ball mill and ball milled for 20 minutes to mix the two uniformly to obtain a graphene-reinforced polyimide resin.
[0039] (2) Hollow carbon fibers were prepared using coaxial electrospinning technology. 80 parts of hollow carbon fibers were placed in a vacuum reactor and evacuated. Then, 10 parts of heavy oil at 80°C were slowly injected into the reactor, stirring while injecting, so that the hollow carbon fibers fully absorbed the heavy oil. After the excess heavy oil that was not absorbed was discharged, 10 parts of liquid UV-curable epoxy resin were injected into the reactor to coat the surface and end faces of the hollow carbon fibers. Finally, the treated hollow carbon fibers were taken out of the reactor, dispersed by air flow, and then placed under ultraviolet light for curing to obtain liquid-core carbon fibers filled with heavy oil.
[0040] Using hollow halloysite nanotubes and heavy oil as raw materials, heavy oil-filled liquid-core halloysite nanotubes were prepared in the same way.
[0041] (3) Prepare the materials according to the formula, put the liquid core carbon fiber, liquid core halloysite nanotubes, graphene-enhanced polyimide resin, barium sulfate, potassium sodium hexatitanate, stannous sulfide, phosphorus flake graphite, and nano silicon carbide wafers into a high-speed mixer, and mix them at a speed of 3000 rpm for 3 minutes to obtain a friction material mixture. Put the friction material mixture into a hot mold heated to 140°C in advance, and pressurize it to 400 kg / cm after the mold is closed. 2 The mold was opened after 5 minutes of holding, and the green body was obtained. The green body was heated to 145° C. and cured for 5 hours to obtain the target friction material.
[0042] Example 2
[0043] The formulation of the low dust emission friction material is:
[0044] 13 parts of liquid core carbon fiber;
[0045] 6 parts of liquid core halloysite nanotubes;
[0046] 12 parts of graphene-enhanced polyimide resin;
[0047] 25 parts of barium sulfate;
[0048] 18 parts of potassium sodium hexatitanate;
[0049] 8 parts of stannous sulfide;
[0050] 8 parts of graphite flakes;
[0051] 10 nano-SiC wafers (0.2 mm in diameter, about 500 nm in thickness).
[0052] The preparation and method of the low dust emission friction material are as follows:
[0053] (1) Add 1 part of graphene oxide with a particle size of less than 1 μm and 99 parts of polyimide resin into a ball mill, and ball mill for 20 minutes to mix the two evenly to obtain a graphene-reinforced polyimide resin.
[0054] (2) Hollow carbon fibers were prepared using coaxial electrospinning technology. 85 parts of hollow carbon fibers were placed in a vacuum reactor and evacuated. Then, 7.5 parts of heavy oil at 80°C were slowly injected into the reactor, stirring while injecting, so that the hollow carbon fibers fully absorbed the heavy oil. After the excess heavy oil that was not absorbed was discharged, 7.5 parts of liquid UV-curable epoxy resin were injected into the reactor to coat the surface and end face of the hollow fiber. Finally, the hollow carbon fibers were taken out of the reactor, dispersed by air flow, and then placed under UV light for curing to obtain liquid-core carbon fibers filled with heavy oil.
[0055] Using hollow halloysite nanotubes and heavy oil as raw materials, heavy oil-filled liquid-core halloysite nanotubes were prepared in the same way.
[0056] (3) Prepare the materials according to the formula, put the liquid core carbon fiber, liquid core halloysite nanotubes, graphene-enhanced polyimide resin, barium sulfate, potassium sodium hexatitanate, stannous sulfide, phosphorus flake graphite, and nano silicon carbide wafers into a high-speed mixer, and mix them at a speed of 3000 rpm for 3 minutes to obtain a friction material mixture. Put the friction material mixture into a hot mold preheated to 140°C, and pressurize it to 250kg / cm after the mold is closed. 2 The mold was opened for 8 minutes to obtain a green body, which was heated to 150° C. and cured for 3 hours to obtain the target friction material.
[0057] Example 3
[0058] The formulation of the low dust emission friction material is:
[0059] 15 parts of liquid core carbon fiber;
[0060] 6 parts of liquid core halloysite nanotubes;
[0061] 10 parts of graphene-enhanced polyimide resin;
[0062] 30 parts of barium sulfate;
[0063] 19 parts of potassium sodium hexatitanate;
[0064] 5 parts of stannous sulfide;
[0065] 5 parts of graphite flakes;
[0066] 10 nano-SiC wafers (0.25 mm in diameter and about 400 nm in thickness).
[0067] The preparation and method of the low dust emission friction material are as follows:
[0068] (1) 0.7 parts of graphene oxide with a particle size of less than 1 μm and 99.3 parts of polyimide resin were added to a ball mill and ball milled for 20 minutes to mix the two uniformly to obtain a graphene-reinforced polyamide resin.
[0069] (2) Hollow carbon fibers were prepared using coaxial electrospinning technology. 90 parts of hollow carbon fibers were placed in a vacuum reactor and evacuated. Then, 5 parts of heavy oil at 80°C were slowly injected into the reactor, stirring while injecting, so that the hollow carbon fibers fully absorbed the heavy oil. After the excess heavy oil that was not absorbed was discharged, 5 parts of liquid UV-curable epoxy resin were injected into the reactor to coat the surface and end face of the hollow fiber. Finally, the hollow carbon fibers were taken out of the reactor, dispersed by air flow, and then placed under UV light for curing to obtain liquid-core carbon fibers filled with heavy oil.
[0070] Using hollow halloysite nanotubes and heavy oil as raw materials, heavy oil-filled liquid-core halloysite nanotubes were prepared in the same way.
[0071] (3) Prepare the materials according to the formula, put the liquid core carbon fiber, liquid core halloysite nanotubes, graphene-enhanced polyimide resin, barium sulfate, potassium sodium hexatitanate, stannous sulfide, phosphorus flake graphite, and nano silicon carbide wafers into a high-speed mixer, and mix them at a speed of 3000 rpm for 3 minutes to obtain a friction material mixture. Put the friction material mixture into a hot mold heated to 150°C in advance, and pressurize it to 400 kg / cm after closing the mold. 2 The mold was opened after 5 minutes of holding, and the green body was obtained. The green body was heated to 160° C. and cured for 2 hours to obtain the target friction material.
[0072] Comparative Example 1
[0073] The formulation of the low dust emission friction material is:
[0074] 10 parts of uncapped liquid core carbon fiber;
[0075] 3 parts of uncapped liquid-core halloysite nanotubes;
[0076] 15 parts of graphene-enhanced polyimide resin;
[0077] 20 parts of barium sulfate;
[0078] 22 parts of potassium sodium hexatitanate;
[0079] 10 parts of stannous sulfide;
[0080] 10 parts of phosphorus flake graphite;
[0081] 10 nano-SiC wafers (0.2 mm in diameter, about 350 nm in thickness).
[0082] The preparation and method of the low dust emission friction material are as follows:
[0083] (1) 0.5 parts of graphene oxide with a particle size of less than 1 μm and 99.5 parts of polyimide resin are added to a ball mill and ball milled for 20 minutes to mix the two uniformly to obtain a graphene-reinforced polyimide resin.
[0084] (2) Hollow carbon fibers were prepared by coaxial electrospinning technology. 80 parts of hollow carbon fibers were placed in a vacuum reactor and evacuated. Then, 10 parts of heavy oil at 80°C were slowly injected into the reactor while stirring, so that the hollow carbon fibers fully absorbed the heavy oil. The solid matter was taken out and the excess heavy oil that was not absorbed was separated and removed to obtain a liquid core carbon fiber filled with heavy oil and not capped.
[0085] Using hollow halloysite nanotubes and heavy oil as raw materials, heavy oil-filled uncapped liquid-core halloysite nanotubes were prepared in the same manner.
[0086] (3) Prepare the materials according to the formula, put the uncapped liquid core carbon fiber, uncapped liquid core halloysite nanotube, graphene-enhanced polyimide resin, barium sulfate, potassium sodium hexatitanate, stannous sulfide, phosphorus flake graphite, and nano silicon carbide wafer into a high-speed mixer, and mix at a speed of 3000 rpm for 3 minutes to obtain a friction material mixture. Put the friction material mixture into a hot mold preheated to 140°C, and pressurize it to 400 kg / cm after the mold is closed. 2 The mold was opened after 5 minutes of holding, and the green body was obtained. The green body was heated to 145° C. and cured for 5 hours to obtain the target friction material.
[0087] Comparative Example 2
[0088] The formulation of the low dust emission friction material is:
[0089] 13 parts of liquid core carbon fiber;
[0090] 15 parts of graphene-enhanced polyimide resin;
[0091] 20 parts of barium sulfate;
[0092] 22 parts of potassium sodium hexatitanate;
[0093] 10 parts of stannous sulfide;
[0094] 10 parts of phosphorus flake graphite;
[0095] 10 nano-SiC wafers (0.2 mm in diameter, about 350 nm in thickness).
[0096] The preparation and method of the low dust emission friction material are as follows:
[0097] (1) 0.5 parts of graphene oxide with a particle size of less than 1 μm and 99.5 parts of polyimide resin are added to a ball mill and ball milled for 20 minutes to mix the two uniformly to obtain a graphene-reinforced polyimide resin.
[0098] (2) Hollow carbon fibers were prepared using coaxial electrospinning technology. 80 parts of hollow carbon fibers were placed in a vacuum reactor and evacuated. Then, 10 parts of heavy oil at 80°C were slowly injected into the reactor, stirring while injecting, so that the hollow carbon fibers fully absorbed the heavy oil. After the excess heavy oil that was not absorbed was discharged, 10 parts of liquid UV-curable epoxy resin were injected into the reactor to coat the surface and end face of the hollow fiber. Finally, the treated hollow carbon fibers were taken out of the reactor, dispersed by airflow, and then placed under UV light for curing to obtain liquid-core carbon fibers filled with heavy oil.
[0099] (3) Prepare the materials according to the formula, put the liquid core carbon fiber, graphene-enhanced polyimide resin, barium sulfate, potassium sodium hexatitanate, stannous sulfide, phosphorus flake graphite, and nano silicon carbide wafer into a high-speed mixer, and mix them at a speed of 3000 rpm for 3 minutes to obtain a friction material mixture. Put the friction material mixture into a hot mold preheated to 140°C, and pressurize it to 400kg / cm after closing the mold. 2 The mold was opened after 5 minutes of holding, and the green body was obtained. The green body was heated to 145° C. and cured for 5 hours to obtain the target friction material.
[0100] Comparative Example 3
[0101] The formulation of the low dust emission friction material is:
[0102] 10 parts of ordinary carbon fiber;
[0103] 3 parts of ordinary halloysite nanotubes;
[0104] 15 parts of graphene-enhanced polyimide resin;
[0105] 20 parts of barium sulfate;
[0106] 22 parts of potassium sodium hexatitanate;
[0107] 10 parts of stannous sulfide;
[0108] 10 parts of phosphorus flake graphite;
[0109] 10 nano-SiC wafers (0.2 mm in diameter, about 350 nm in thickness).
[0110] The preparation and method of the low dust emission friction material are as follows:
[0111] (1) 0.5 parts of graphene oxide with a particle size of less than 1 μm and 99.5 parts of polyimide resin are added to a ball mill and ball milled for 20 minutes to mix the two uniformly to obtain a graphene-reinforced polyimide resin.
[0112] (2) Prepare the materials according to the formula, put carbon fiber, halloysite nanotubes, graphene-enhanced polyimide resin, barium sulfate, potassium sodium hexatitanate, stannous sulfide, graphite flakes, and nano silicon carbide chips into a high-speed mixer, and mix them at a speed of 3000 rpm for 3 minutes to obtain a friction material mixture. Put the friction material mixture into a hot mold preheated to 140°C, and pressurize it to 400 kg / cm after closing the mold. 2 The mold was opened after 5 minutes of holding, and the green body was obtained. The green body was heated to 145° C. and cured for 5 hours to obtain the target friction material.
[0113] In order to fully understand the performance of the friction materials prepared in Examples 1-3 and Comparative Examples 1-3, they were made into brake pads (size 120*44*13mm) and then a series of tests were carried out. Various friction properties were tested according to the method in SAE J2522, including average friction coefficient, first decay friction coefficient, second decay friction coefficient and weight wear, and PM10 friction dust emission was tested according to the GTRWLTP test method. The test results of different samples are shown in Table 1.
[0114] Table 1 Comparison of performance test results of different brake pads
[0115]
[0116] As shown in Table 1, compared with the uncapped liquid core fiber in Comparative Example 1, the single liquid core fiber in Comparative Example 2, and the ordinary fiber without liquid core in Comparative Example 3, the PM10 dust emission of the friction material obtained by coating and capping the liquid core fiber with UV-curable epoxy resin in Examples 1-3 of the present invention is greatly reduced, and the friction coefficient is stable and the wear amount is small. This is because when the liquid core fiber in Comparative Example 1 is not coated, the liquid stored inside it will be discharged prematurely. The premature concentrated discharge of liquid will not only reduce the friction coefficient, but also the wear particles in the later stage cannot be agglomerated due to the premature emptying of the liquid in the fiber, and finally a large amount of PM10 emissions are generated; the single liquid core fiber in Comparative Example 2 lacks the ability to agglomerate fine dust particles, and cannot achieve the best effect of reducing PM10 emissions; the ordinary fiber in Comparative Example 3 has no dust agglomeration ability at all, resulting in higher PM10 emissions.
Claims
1. A liquid core fiber, characterized in that: The liquid-core fiber comprises a hollow fiber and a liquid, wherein the liquid is filled in a cavity inside the hollow fiber.
2. The liquid core fiber according to claim 1, characterized in that: The liquid core fiber also includes epoxy resin, and the epoxy resin is coated on the surface and both ends of the hollow fiber.
3. The liquid core fiber according to claim 1 or 2, characterized in that: The hollow fiber is selected from at least one of hollow carbon fiber and hollow halloysite nanotube, and the liquid is specifically heavy oil.
4. A method for preparing a liquid core fiber, characterized in that The method comprises: placing the hollow fiber in a sealed container, adding a liquid at 80-120°C for adsorption after vacuuming, and finally adding epoxy resin to coat and end-cap the hollow fiber.
5. The method according to claim 4, characterized in that: The epoxy resin is specifically a liquid ultraviolet-curable epoxy resin; after the epoxy resin is added, the solid is separated from the sealed container and dispersed, and then irradiated with ultraviolet light to fully cure it.
6. Low PM10 emission friction material based on liquid core fiber, characterized by: The friction material comprises, by weight, 13-33 parts of liquid core fiber, 10-15 parts of adhesive, 15-30 parts of friction modifier, and 25-55 parts of friction filler. The liquid core fiber is selected from any one of claims 1-3.
7. The friction material according to claim 6, characterized in that: The adhesive is specifically a graphene-enhanced polyimide resin, and the graphene content is 0.5wt%-1wt%, and the graphene is specifically graphene oxide with a particle size of <1 micron; the friction modifier is selected from at least one of stannous sulfide, graphite flakes, and nano silicon carbide chips; the friction filler is selected from at least one of barium sulfate and potassium sodium hexatitanate.
8. The friction material according to claim 6, characterized in that: The friction material comprises, by weight, 10-15 parts of liquid core carbon fiber, 3-8 parts of liquid core halloysite nanotubes, 10-15 parts of graphene-enhanced polyimide resin, 5-10 parts of stannous sulfide, 5-10 parts of phosphorus flake graphite, 5-10 parts of nano silicon carbide chips, 10-25 parts of barium sulfate, and 15-30 parts of potassium sodium hexatitanate.
9. The method for preparing the friction material with low dust emission according to claim 6, characterized in that The method comprises: preparing raw materials according to a formula, mixing the raw materials and then performing molding.
10. The method according to claim 9, characterized in that: The raw materials are mixed evenly in a high-speed mixer at a speed of 2000-5000rpm, the temperature during molding is 135-150℃, and the pressure is 200-500kg / cm 2 The green body obtained by compression molding is placed at 145-160°C for curing.
Citation Information
Patent Citations
Preparation method of modified carbon fiber friction particle
CN107936916A
Method for producing friction discs from fibre-reinforced ceramic materials
EP2058546A2
Luminous synthetic fiber
JP2020070525A